Facilitating regular Physical Education for students with disability—PE teachers' views - Bertills, Karin; Björk, Maria (Frontiers in Sports and Active Living, 2024)
The objective of this study is to describe how Physical Education (PE) teachers work to facilitate participation for students with disability in compulsory, mainstream inclusive, secondary school. Inclusive school-based Physical Education (PE) is an important context for students to share the benefits of physical activities with peers, especially for students with disability whose opportunities for participation in extracurricular physical activity are limited. Two focus group interviews were performed with eight experienced PE teachers who teach students with disability in regular PE. Qualitative content analysis was used to analyze the interviews. Two themes emerged, the importance of having a structured and welcoming environment and the need to adapt the PE environment. Student mastery experiences is emphasized and achieved by teaching approaches encouraging peer collaboration before physical performance and competition. Key aspects to participation for students with disabilities are inclusive mindsets, proper preparation, and adaptations. Special arrangements when participation in-class is not possible require regular and close teacherstudent communication and, when needed, additional support. Experiences of participation are important matters for further advancement of equality and social inclusion for students with disability. Schools need to develop support structures to provide students with disability with 'reallife' experiences that optimize participation.